Willingness to purchase safer vehicles: a study base on Malaysia B40 income group - Mohd Radzi Abu Mansor,; Khairil Anwar Abu Kassim,; Zulhaidi Mohd Jawi, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Passenger car is one of the most preferable modes of transportation used in Malaysia. It is very important to keep safety features as suggested by ASEAN NCAP in a vehicle that we used in order to avoid and minimize the accident occurrence. However, new vehicle with advanced safety features is more expensive, where there are certain people that cannot afford to buy an expensive car such as B40 consumers (bottom 40% which household income is under RM3,860.00). According to the Maslow’s Hierarchy of Needs, the lower income group consumer will put the physiological need first rather than safety needs. As they cannot afford to buy a new car with extra safety features, they bought and old vehicle which currently has less safety features but with cost of maintenance were rather high. In this study – with regard to owning vehicles, specifically cars – the willingness to buy safer vehicle among lower group based on economic strength will be analyze.